Reliability test of a questionnaire to investigate behaviour of using traditional medicines among urban students of Elementary School - Cahyani, Riska; Widayati, Aris (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Introduction. The use of traditional medicine among the adult population is prevalent. Previous studies have explored the use of traditional medicine among adults. However, traditional medicine usage among adolescents is still rare, especially among elementary school students. Therefore the instruments for research on the use of traditional medicine among adolescents are also still limited. Objective. This study aims to calculate the reliability scale of a questionnaire based on the Theory of Planned Behavior. The questionnaire can be used to explore the behavior of using traditional medicine among elementary school students. Methods. The tested instrument has been assessed for its content validity using a professional judgement approach and language clarity. In this study, instrument reliability was calculated using Cronbach Alpha approach. The test respondents were elementary school students in Yogyakarta City namely SD Negeri Ungaran Yogyakarta. Fifty respondents were selected using purposive sampling and given a self-asministered questionnaire. Data were entered and calculated for Cronbach Alpha using SPSS software. Results. Twelve percent of the 50 data sets were ineligible for inclusion due to incomplete answers, resulting in 44 data sets (88%) being analysed. The analysis produces a Cronbach's Alpha scale of 0.840 with 24 items in the questionnaire. Conclusion. The conclusion is that the instrument is reliable because the scale of Cronbach's Alpha is more than 0.60 as the standard point. It can be used to investigate a behaviour regarding traditional medicines usage among Elementary Students in urban areas.